Feature : 'Look happy dear, you've just made a discovery'. (24th October 2017) - Tesh, Sarah; Wade, Jess
Abstract: Sarah Tesh and Jess Wade describe Jocelyn Bell Burnell's highs and lows, as revealed in her recent IOP President's Medal lecture